Personhood and status of legal persons in private international law. (4th May 2019) - Robb, John
Abstract : In Investec v Glenalla [2018] UKPC 7, the Privy Council divided 3-2 on whether a Guernsey court should apply a provision of Jersey trusts law to limit the liability (under contracts governed by English law) of two Guernsey companies, former trustees of a Jersey trust. The majority's reasoning rests on a newly-discovered rule of common law. This article suggests that there is no such rule. There is a rule that English law will recognise not only the existence of a foreign legal person but also its essential attributes; however, that rule applies only (i) to "entities" which qualify as legal persons within the legal system that constituted them, and (ii) to "essential" as opposed to merely contingent attributes of the entity. The fact that an entity's liabilities to third parties may be limited by a provision of its domestic law does not qualify as an essential attribute for these purposes.